Law and Cinema: An Introduction - Yu. V. Erokhina; N. M. Galkina; E. A. Tokhtueva (Теоретическая и прикладная юриспруденция)
The article reveals the main trends of the “Law and Cinema” scholarly movement, which has been actively explored in the foreign legal literature in recent decades. An attempt is made to review open academic and empirical sources to identify the relationship between law and cinema, key works and contemporary publications on this topic, as well as the available criticism of research in the ﬁeld of law and cinema justiﬁcation. A deﬁnition of the scope of the “Law and Cinema” research ﬁeld in the context of the Russian research ﬁeld, the subject matter and research methodology are suggested.